The efficacy and safety of lenvatinib plus transarterial chemoembolization in combination with PD-1 antibody in treatment of unresectable recurrent hepatocellular carcinoma: a case series report - Mu, Chunyang; Shen, Junyi; Zhu, Xinrui; Peng, Wei; Zhang, Xiaoyun; Wen, Tianfu (Frontiers in oncology, 2023)
To explore the safety and efficacy of lenvatinib in combination with trans-arterial chemoembolization (TACE) and programmed death receptor 1 (PD-1) antibody in the treatment of unresectable recurrent hepatocellular carcinoma (urHCC). The clinical data of 16 patients with unresectable recurrent hepatocellular carcinoma admitted to the Department of Liver Surgery and Liver Transplantation Center, West China Hospital, Sichuan University, and received the conversion therapy of lenvatinib + TACE + PD-1 antibody between January 2019 and January 2022 were retrospectively analyzed. There were 25% (4/16) patients suffering from grade 3 adverse events and no patients suffering from grade 4 or higher adverse events. After 4 months of treatment of 16 patients, according to the modified Response Evaluation Criteria in Solid Tumors (mRECIST), two, five, three, and six cases were in complete response (CR), partial response (PR), stable disease (SD), and progressive disease (PD), respectively, and the objective response rate (ORR) was 43.8% (7/16). The 1-year overall survival (OS) rate and 1-year progression-free survival (PFS) rate were 86.2% and 46.9%, respectively. In our subgroup analysis, the ORR of patients with multiple lesions reached up to 60%, which was higher than that of patients with single lesions. Lenvatinib in combination with TACE and PD-1 antibody is safe and effective in the treatment of unresectable recurrent hepatocellular carcinoma.